Nutritional treatment of patients in the perioperative period - literature review - Miśkiewicz, Marek; Noga, Rafał; Marcinkowska, Jagoda; Ptak, Jakub; Herc, Adrian; Sawczuk, Marcelina; Koczkodon, Karolina; Teska, Victoria; Perłowski, Jakub; Krompiewski, Mariusz (Quality in Sport, 2024)
There are many factors influencing the condition of surgical patients. One undoubtedly important one is the nutritional status of the patient. Over the years, many guidelines have been developed to reduce malnutrition and improve the nutritional status of surgical patients. It has been proven in numerous studies that malnutrition worsens the prognosis of patients undergoing surgery. Numerous advances in many fields of medicine, such as better conservative treatment, development of surgical techniques or new surgical instruments, have contributed to improving the prognosis of patients in the postoperative period. Inadequate nutritional status is one of the main factors negatively affecting this process . Perioperative nutritional support, as part of the ERAS (Enhanced Recovery After Surgery) protocol, has proven to be crucial in improving surgical outcomes . By introducing a nutritional assessment even before planned procedures, we can improve the patient’s condition with oral supplements and immunomodulatory preparations. This can reduce the length of patient hospitalization and mortality. In this review, we will focus on the latest developments and available research on these issues.